Stray Currents in Livestock Farming: Electrical Diagnosis in Farms - Quentin Lagarde; Bruno Beillard; Daan Marcuzzi; Serge Mazen; Julien Leylavergne (Agriculture, 2023)
For several years, farmers have been questioning the effects of electromagnetic fields and stray electrical currents on the health of their animals. Observing changes in behavior or a decline in livestock productivity, farmers suspect that electrical installations on or near the farm may be responsible. Indeed, these systems can generate fault currents or stray currents, some of which may pass through the animals, affecting their well-being and productivity. To identify the origin and address this issue, an electrical diagnosis can be performed. In this study, diagnostics were carried out in eleven bovine farms considered “healthy”. These measurements included earth resistance equipment insulation resistance, continuity, leakage currents, as well as contact and step voltages, with some farms presenting non-conformities. This study will better understand the potential links between electrical installations and animal well-being, correlate the results of this study with those obtained in diagnostics conducted on farms experiencing such concerns and implement appropriate preventative and corrective measures.